The Cultural Net Early Modern Drama as a Paradigm - Küpper, Joachim (De Gruyter, 2018)
I developed the basic theoretical approach here outlined, which consists in a network theory of cultural (specifically literary) production. The main area of exemplification for the theoretical assumptions, early modern European drama, was chosen to accord with one of my primary fields of expertise. Over the years during which I was able to devote myself to this project-for which we created the name "DramaNet"-I profited enormously from working with the members of my team, who introduced me to ramifications of the questions pertaining to the field of exemplification previously unknown to me. The present book will refer to their publications wherever this is indicated according to standards of scholarly ethics; in order to provide some orientation, I will briefly characterize the thematic and methodological frames of the various more specialized studies resulting from the research team's endeavors in the last section of the chapter "Outline of the Argument".